Relationship between dietary factors and bodily iron status among Japanese collegiate elite female rhythmic gymnasts - Kokubo, Y.; Yokoyama, Y.; Kisara, K.; Ohira, Y.; Sunami, A.; Yoshizaki, T.; Tada, Y.; Ishizaki, S.; Hida, A.; Kawano, Y. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
This cross-sectional study explored the prevalence of iron deficiency (ID) and associations between dietary factors and incidence of ID in female rhythmic gymnasts during preseason periods. Participants were 60 elite collegiate rhythmic gymnasts (18.1 ± 0.3 years [M ± SD]) who were recruited every August over the course of 8 years. Participants were divided into 2 groups according to the presence or absence of ID. Presence of ID was defined either by ferritin less than 12 µg/L or percentage of transferrin saturation less than 16%. Anthropometric and hematologic data, as well as dietary intake, which was estimated via a semiquantitative food frequency questionnaire, were compared. ID was noted in 48.3% of participants. No significant group-dependent differences were observed in physical characteristics, red blood cell counts, hemoglobin, hematocrit, haptoglobin, or erythropoietin concentrations. The ID group had a significantly lower total iron-binding capacity; serumfree iron; percentage of transferrin saturation; ferritin; and intake of protein, fat, zinc, vitamin B2, vitamin B6, beans, and eggs but not iron or vitamin C. The recommended dietary allowance for intake of protein, iron, zinc, and various vitamins was not met by 30%, 90%, 70%, and 22%-87% of all participants, respectively. Multiple logistic analysis showed that protein intake was significantly associated with the incidence of ID (odds ratio = 0.814, 95% confidence interval [0.669, 0.990], p = .039). Participants in the preseason`s weightloss periods showed a tendency toward insufficient nutrient intake and were at a high risk for ID, particularly because of lower protein intake.